The Role of Self-Regulation and Emotional Intelligence in Enhancing Problem-Solving Skills among Organizationally Active Students - Shefia Dewitasari; Trubus Raharjo (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study examined the relationship between self-regulation and emotional intelligence and problem-solving ability among students actively involved in organizations. A quantitative correlational design was used with 104 respondents selected through quota sampling at Mua Kudus University. The research instruments were self-regulation, emotional intelligence, and problem-solving scales. Data were analyzed using Pearson product-moment correlation and multiple regression. The results showed a very significant positive relationship between self-regulation and emotional intelligence and problem-solving ability (R = 0.743; p < 0.01), with an effective contribution of 55.2%. Self-regulation was positively associated with problem-solving ability (r = 0.716; p < 0.01) and contributed 51.2%, while emotional intelligence also showed a significant positive relationship (r = 0.601; p < 0.01) with a 36.2% contribution. These findings indicate that students with stronger self-regulation and emotional intelligence tend to solve organizational problems more effectively. The study suggests that universities should strengthen these capacities through targeted training programs for organizational effectiveness and student development.